A new era in the management of spinal metastasis - Morimoto, Tadatsugu; Toda, Yu; Hakozaki, Michiyuki; Paholpak, Permsak; Watanabe, Kazuyuki; Kato, Kinshi; Tsukamoto, Masatsugu; Hirata, Hirohito; Kaneuchi, Yoichi; Tome, Yasunori; Nagamine, Satomi; Nishida, Kotaro; et al. (Frontiers in Oncology, 2024)
Despite the recent advances in cancer treatment, the incidence of patients with spinal metastases continues to grow along with the total number of cancer patients. Spinal metastases can significantly impair activities of daily living (ADL) and quality of life (QOL), compared with other types of bone metastases, as they are characterized with severe pain and paralysis caused by skeletal-related events. Reduced ADL can also lead to treatment limitations as certain anticancer agents and radiation therapy are not compatible treatments; thus, leading to a shorter life expectancy. Consequently, maintaining ADLs in patients with spinal metastases is paramount, and spine surgeons have an integral role to play in this regard. However, neurosurgeon, orthopedic and spinal surgeons in Japan do not have a proactive treatment approach to spinal metastases, which may prevent them from providing appropriate treatment when needed (clinical inertia). To overcome such endemic inertia, it is essential for 1) spine surgeons to understand and be more actively involved with patients with musculoskeletal disorders (cancer locomo) and cancer patients; 2) the adoption of a multidisciplinary approach (coordination and meetings not only with the attending oncologist but also with spine surgeons, radiologists, rehabilitation specialists, and other professionals) to preemptive treatment such as medication, radiotherapy, and surgical treatment; and 3) the integration of the latest findings associated with minimally invasive spinal treatments that have expanded the indications for treatment of spinal metastases and improved treatment outcomes. This heralds a new era in the management of spinal metastases.